2007
DOI: 10.1182/blood-2007-02-074617
|View full text |Cite
|
Sign up to set email alerts
|

The new tumor-suppressor gene inhibitor of growth family member 4 (ING4) regulates the production of proangiogenic molecules by myeloma cells and suppresses hypoxia-inducible factor-1 α (HIF-1α) activity: involvement in myeloma-induced angiogenesis

Abstract: IntroductionAngiogenesis has a critical role in the pathophysiology and progression of multiple myeloma (MM) supporting the growth and survival of MM cells. [1][2][3][4][5] The angiogenic process in MM is sustained mainly by the overexpression of proangiogenic factors directly by MM cells including VEGF, 6 angiopoietin-1 (ANG-1), 7 osteopontin (OPN), . 9 Nevertheless, the molecular mechanisms underlying the regulation of angiogenesis in MM have not been completely elucidated.The new candidate tumor-suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
125
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 45 publications
(87 reference statements)
9
125
0
1
Order By: Relevance
“…The capacity of HIF-1a to regulate VEGFA and IL8 gene expression by MM cells confirmed our previous data, 27,39 and supports HIF-1a as a key regulator of angiogenesis also in MM cells because VEGF 9,10 and at least in part of IL-8 39,40 are well-known factors involved in MM-induced angiogenesis. CCL2 and MMP9 could be also involved in the pro-angiogenic role of HIF-1a, because both cytokines are produced by MM cells and contribute to angiogenesis and BM spreading.…”
Section: Discussionsupporting
confidence: 88%
“…The capacity of HIF-1a to regulate VEGFA and IL8 gene expression by MM cells confirmed our previous data, 27,39 and supports HIF-1a as a key regulator of angiogenesis also in MM cells because VEGF 9,10 and at least in part of IL-8 39,40 are well-known factors involved in MM-induced angiogenesis. CCL2 and MMP9 could be also involved in the pro-angiogenic role of HIF-1a, because both cytokines are produced by MM cells and contribute to angiogenesis and BM spreading.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, ING4 down-regulated angiogenesis related molecules including IL-8 and HIF-1α [117,119]. In line with these observations it has been shown that ING4 nuclear level is reduced in myeloma cells as compared to normal plasma cells, and that ING4 regulates IL-8 and OPN production by myeloma cells both in normoxia and hypoxia [95]. In addition, ING4 has a suppressive effect on HIF-1α activity in myeloma cells because blocking ING4 in myeloma cells increases both HIF-1α activity and the expression of its target gene NIP-3 [95].…”
Section: Genes Involved In the Regulation Of The Pro-angiogenic Profisupporting
confidence: 63%
“…Studies indicate that myeloma cells and BM stromal cells [94,95] directly produce IL-8, and elevated BM levels of IL-8 have been demonstrated in MM patients [95]. Tumor cell expression of IL-8 has been linked to the metastatic potential of many solid tumors [96,97].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that ING4 is a tumor suppressor for it intervenes the activity of hypoxia inducible factor (HIF) which has an important positive role in angiogenesis and tumorigenesis. HIF promote tumor angiogenesis by inducing VEGF and other factors (Ozer et al, 2005;Colla et al, 2007). Thus, the up-regulation of VEGF by miR-150 may be mediated by ING4 (Brahimi-Horn and Pouyssegur, 2006).…”
Section: Discussionmentioning
confidence: 99%